A water-stable terbium metal–organic framework as a highly sensitive fluorescent sensor for nitrite. Issue 18 (6th August 2020) - Min, Hui; Han, Zongsu; Wang, Mengmeng; Li, Yongjie; Zhou, Tianze; Shi, Wei; Cheng, Peng
Abstract : A terbium metal–organic framework was synthesized for highly sensitive nitrite detection. The mechanism of the quenching process was also studied in detail. Abstract : A novel water-stable Tb-based metal–organic framework (Tb-MOF), namely {[Tb(CA)(OA)0.5 (H2 O)2 ]·H2 O} n (H2 CA = chelidonic acid; H2 OA = oxalic acid), was synthesized via a solvothermal method. Tb-MOF was studied for its highly sensitive detection towards nitrite, which is a hazardous chemical in water and food. As a luminescent sensor, Tb-MOF displays a linear detection range between 0 and 15.6 μM, with a limit of detection of 28.25 nM. Dynamic quenching process was observed in this system and was studied in detail. A mechanism study revealed that the fluorescence response of Tb-MOF towards nitrite was due to the energy transfer from the sensitized Tb 3+ ion to the nitrite.